Export activity, innovation and institutions in Southern European nascent entrepreneurship - Helena Marques (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
This paper studies the role of personal characteristics, perceptual variables and country-level conditioning (financial environment, government quality and support, education quality and entrepreneurship know-how, innovation environment and support, business infrastructure, entrepreneurial culture and society, and gender roles) in explaining the export propensity and intensity of nascent entrepreneurs in four Southern European countries (Portugal, Spain, Italy and Greece), using Total Early-stage Entrepreneurial Activity (TEA) data from the Global Entrepreneurship Monitor (GEM) dataset in 2003-2010. Due to the nascent nature of the business, export activity is starting or about to start at the time of the survey and, for that reason, it cannot be studied using theoretical frameworks based on productivity heterogeneity, which has not yet been measured. In this sample of nascent businesses, there is no evidence of a selection effect into exporting and the individual-level factors influencing export propensity and intensity are identical. The most relevant individual-level variables facilitating export activity are new products, new technology, graduate education, and entrepreneurship networks. The most relevant country-level factors facilitating export activity are the availability of funding, the national government's macroeconomic support, and the support for new technology.
Keywords: F14; J24; L26; O43; 330; entrepreneurship; exporting; innovation; institutions; Southern Europe